ESTIMATION OF INTERIOR TEMPERATURE OF AN ELECTRIC OVEN - Ogwola, Peter; Sullayman, Muhammad Bello (FUDMA JOURNAL OF SCIENCES, 2021)
This paper is aimed at estimating interior temperature of an electric oven with respect to the jacket temperature. A discrete dynamic model of first order difference equation is described for the system. Kalman filtering technique is applied to the discrete dynamic model for estimation of the interior temperature. A computer program is written to simulate the system. It was observed that the estimates of the interior temperatures are directly proportional to estimates of the Jacket temperatures with proportionality constant of 0.0009. With this method it is therefore possible to obtain the interior temperature of the electric oven at any given time.